2011
DOI: 10.1084/jem.20111020
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system inflammation induces muscle atrophy via activation of the hypothalamic–pituitary–adrenal axis

Abstract: Systemic and CNS-delimited inflammation triggers skeletal muscle catabolism in a manner dependent on glucocorticoid signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
194
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 180 publications
(205 citation statements)
references
References 76 publications
9
194
0
2
Order By: Relevance
“…The induction of inflammation is most pronounced in the hypothalamus and is not observed in other brain structures such as the cerebral cortex ( Figure 5B). In alignment with previous findings that muscle atrophy during inflammatory stimuli is mediated by hypothalamic–pituitary–adrenal activation, end‐stage KPC‐engrafted animals demonstrate a 1.77 ± 0.19‐fold increase in hypothalamic expression of corticotropin‐releasing hormone ( P  < 0.05) ( Figure 5C) 22, 26…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The induction of inflammation is most pronounced in the hypothalamus and is not observed in other brain structures such as the cerebral cortex ( Figure 5B). In alignment with previous findings that muscle atrophy during inflammatory stimuli is mediated by hypothalamic–pituitary–adrenal activation, end‐stage KPC‐engrafted animals demonstrate a 1.77 ± 0.19‐fold increase in hypothalamic expression of corticotropin‐releasing hormone ( P  < 0.05) ( Figure 5C) 22, 26…”
Section: Resultssupporting
confidence: 90%
“…Muscles with a high preponderance of fast‐twitch fibres, that is, gastrocnemius, tibialis anterior, and quadriceps, were selected for skeletal muscle analysis because they are particularly susceptible to wasting in inflammatory states 26. Indeed, KPC tumour growth induced tissue atrophy in all three of these muscle groups, corresponding to high expression levels of the ubiquitin ligases MAFBx and MuRF1 and their transcriptional inducer FOXO1.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have documented the potential contribution of GC (32), proinflammatory cytokines (33,34), and LPS (35) to this effect. However, recent studies have substantially evidenced that GC were indeed requisite to this process, because activation of the genes involved in muscle atrophy after LPS-induced peripheral inflammation was essentially blocked by adrenalectomy (36). In this study, we observed a strong reduction in the activation of catabolic genes but also of repressor genes of the mTOR anabolic pathway in muscle of endotoxemic hypomSR-BI DAC mice.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, brain-IL1B injection leads to muscle wasting and increases in markers of muscle protein breakdown, such as MURF and Atrogin1. In accordance with the existance of an adrenal-mediated effect, adrenalectomy suppressed IL1B-induced muscle atrophy, whilst glucocorticoid treatment was enough to promote muscle atrophy (Braun et al 2011). Interestingly, in spite of muscle wasting induced by cancer, uremia, or LPS, as well as IL1B-induced anorexia is suppressed by MC4R blockade (Marks et al 2001, 2003, Wisse et al 2001, Cheung et al 2008, Whitaker & Reyes 2008), MC4R-knockout animals are not saved from body lean mass loss after central infusion of IL1B (Braun et al 2011), these findings indicate that different neuronal circuits are involved in the CNS modulation of muscle catabolic programs and that the hypothalamus is crucial for induction and maintenance of the main symptoms of cancer cachexia.…”
Section: Neuroendocrine Regulation Of Cachexia-induced Thermogenesis mentioning
confidence: 53%
“…Although the influence of the hypothalamus on the modutation of lean body mass is clear, the mechanisms are only partially elucidated (Marks et al 2001, 2003, Wisse et al 2001, Cheung et al 2008, Braun et al 2011. The hypothalamic-pituitary-adrenal axis is an important Figure 2 The hypothalamus is at the crossroads of cancer cachexia's main features.…”
Section: Neuroendocrine Regulation Of Cachexia-induced Thermogenesis mentioning
confidence: 99%